(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: Adolescents are a heterogeneous group with special reproductive health needs based on their age, sex, marital status and socioeconomic status. Existing health care system is not capable to respond to adolescents’ demands. Objective: To explore the idea regarding specific centre for adolescents and to identify the components of information and health services rendered through the centre. Method: A cross sectional study was conducted with 70 participants in a half day workshop in the Institute of child and mother health (ICMH) on 9th August’ 2006. The respondents filled up a set questionnaire containing both open and closed questions focusing different issues regarding functioning of an adolescent clinic. The responses were analysed using SPSS program Result: Almost all respondents expressed the need for a separate clinic for adolescents, that should serve both boys and girls (84.3%), health providers at the centre should be doctors from both Paediatrics and Gynae & Obstetrics department (42.9%) and nurses (42.1%) and the working schedule should be similar to existing out patient hours. It was suggested that the clinic should provide counseling on sexuality issues, contraceptive services and special services as required in addition to general health care. About 75% opined that the cost of the services should be same as those of existing out patient services while 52.9% thought that the services should be free. Conclusion: The need for an adolescent clinic was commonly felt and it is recommended to establish adolescent friendly services at ICMH. Key words: Adolescent; Reproductive health; Adolescent friendly service DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9433 JBCPS 2011; 29(3): 133-137